Hadith Tarbawi Learning Model in Forming Students' Pancasila Character - Arcanita, Rapia; Warsah, Idi; Karolina, Asri; Indrawari, Karliana (Madania: Jurnal Kajian Keislaman, 2025)
This study aims to understand the role of character education in higher education in forming students' identity, independence, and responsibility, as well as integrating Pancasila values to enhance the quality of human resources. This study employs a field research design with a grounded theory approach. The participants in this study are lecturers from the Islamic Education program (PAI) at the Faculty of Education/Tarbiyah at IAIN Curup. The primary data sources are lecturers teaching Hadith Tarbawi and students from the PAI program, while secondary data includes lesson plans (RPS), books, and other written materials related to the research. Data collection techniques include observation, interviews, documentation, and literature study. Data analysis techniques involve open coding, axial coding, selective coding, and memoing. The results of this study indicate that the "Hadith Tarbawi Learning Model" is designed to integrate Islamic teachings with Pancasila values, aiming to shape character. This model emphasizes the use of hadith, the sayings and actions of the Prophet Muhammad SAW, as a source of moral and ethical guidance in education. By focusing on character development, this model seeks to instill values such as honesty, justice, cooperation, and wisdom, which align with Pancasila principles. This approach involves various collaborative and interactive learning methods, such as problem-based learning, discussions, and group activities, to foster a deep understanding and internalization of these values among students. This educational approach not only enhances academic abilities but also strives to cultivate graduates who are ethically grounded and capable of positively impacting society. Tujuan penelitian ini adalah untuk mengetahui peran pendidikan karakter di perguruan tinggi dalam membentuk identitas, kemandirian, tanggung jawab siswa, dan mengintegrasikan nilai-nilai Pancasila untuk meningkatkan kualitas sumber daya manusia. Penelitian ini menggunakan jenis penelitian lapangan (field research) dengan pendekatan grounded theory. Subyek penelitian adalah dosen Prodi PAI Fakultas Tarbiyah IAIN Curup. Sumber data primer dosen yang mengajar hadist tarbawi dan mahasiswa Prodi PAI dan data sekunder adalah RPS (Rencana Pembelajaran Semester), buku-buku dan bahan tulisan lain yang terkait penelitian. Tekhik pengumpulan data observasi, wawancara, dokumentasi, serta studi literatur. Tekhnik analisa data yaitu: pengekodean terbuka, pengkodean berporos, pengkode yang terpilih, dan pememoan. Hasil dari penelitian ini menunjukkan “Model Pembelajaran Hadis Tarbawi” dirancang untuk mengintegrasikan ajaran Islam dengan nilai-nilai Pancasila, yang bertujuan untuk membentuk karakter. Model ini menekankan penggunaan hadis, yang merupakan ucapan dan tindakan Nabi Muhammad SAW, sebagai sumber bimbingan moral dan etika pendidikan. Dengan berfokus pada pengembangan karakter, model ini berusaha menanamkan nilai-nilai seperti kejujuran, keadilan, kerja sama, dan kebijaksanaan, yang selaras dengan prinsip Pancasila. Pendekatan ini melibatkan berbagai metode pembelajaran kolaboratif dan interaktif, seperti pembelajaran berbasis masalah, diskusi, dan kegiatan kelompok, untuk menumbuhkan pemahaman yang mendalam dan internalisasi nilai-nilai ini di antara mahasiswa. Strategi pendidikan ini tidak hanya meningkatkan kompetensi akademik tetapi juga bertujuan menghasilkan lulusan yang berlandaskan secara moral dan mampu berkontribusi positif kepada masyarakat.